Online Teaching during the Covid-19 Crisis in Indonesia: Is It Effective? - Hidayat, Nur (International Journal of Social Learning (IJSL), 2022)
The covid-19 plague compels ELT lecturers in Indonesia to move their teaching method from face-to-face to online teaching in a short time suddenly. However, the government has not fulfilled the facilities and infrastructure to do online teaching. This study investigated the effectiveness of online teaching implementation at the university level based on the English lecturers' perceptions. This study involved 46 lecturers from Indonesia in different areas, such as South Kalimantan, East Java, Central Java, West Java, Central Sulawesi, South Sulawesi, and Jakarta. The researcher used two instruments to collect the data: semi-structured interviews and questionnaires. The researcher made the data reduction and displayed to analyze the qualitative data, whereas for quantitative data, the researcher analyzed by statistical calculation. The findings of this study indicated that online teaching implementation was not effective yet. The English lecturers faced several significant challenges during online teaching implementation during the Covid-19 plague.